Proximate Levels of Dog Meat (Canis Lupus Familiaris) in Rantepao, North Toraja Regency, South Sulawesi, Indonesia - Ayu, Azizah Reski Ray; Gobel, Fatmah Afrianty; Arman, Arman (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Background: Currently, dog meat fans are increasing, however, people do not know the dangers of consuming dog meat.Consuming dog meat has the potential to cause bacterial infectionsE. Coli, Salmonella, Anthraxso hepatitis. In addition, dog meat can increase the risk of bacterial infection by up to 20 times. Aim: The purpose of this study was to analyze the proximate levels of dog meat, analyze the determinant factors and analyze the frequency of dog meat consumption in the community. Method:This study is a laboratory study with dog meat samples from Rante Pao District, Kab. North Toraja. Results:The proximate levels carried out on dog meat found water content of 69%, ash content of 1%, fat content of 6.01%, protein content of 21.19% and carbohydrates of 2.19%. Dog meat if it is often consumed continuously will be harmful to the body because of the high water content in dog meat, where the level of microbial contamination or parasite growth is faster in meat. The determinant factor is the community in Kec. Rantepao Kab. North Toraja believes in the myth that eating dog meat can increase endurance and reduce the risk of contracting dengue fever. Conclusion: It is recommended to the public not to consume dog meat.